Daya Perlokusi pada Implikatur Percakapan dalam Anime Tsuki Ga Kirei - Widya Kusuma, Ni Made Yunita; Indra Pradhana, Ngurah (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2022)
The goals of this research are to find and describe the kinds of conversational implicature and the power of perlocutionary effect on conversational implicature in Anime Tsuki Ga Kirei. The theories that are used come from Yule about classification of implicature and perlocutionary act from Austin. The method that used is descriptive qualitative method. The result shows that particularized conversational implicature were found to be more than generalized conversational implicature. Because, the additional knowledge possessed by each character was not equal. Meanwhile, scalar implicature and conventional implicature were not found. The perlocutionary effect on generalized implicature is in line with the implications of utterance. Then, perlocutionary effect in particularized conversational implicature are 11 data know the special knowledges and in line with the implications of utterance, 3 data know the special knowledges but not in line with the implications, and 1 data did not know the special knowledges and not in line with the implications.